Right Ventricular Response to Acute Hypoxia Exposure: A Systematic Review - Mamazhakypov, Argen; Sartmyrzaeva, Meerim; Kushubakova, Nadira; Duishobaev, Melis; Maripov, Abdirashit; Sydykov, Akylbek; Sarybaev, Akpay (Frontiers in Physiology, 2022)
Background: Acute hypoxia exposure is associated with an elevation of pulmonary artery pressure (PAP), resulting in an increased hemodynamic load on the right ventricle (RV). In addition, hypoxia may exert direct effects on the RV. However, the RV responses to such challenges are not fully characterized. The aim of this systematic review was to describe the effects of acute hypoxia on the RV in healthy lowland adults. Methods: We systematically reviewed PubMed and Web of Science and article references from 2005 until May 2021 for prospective studies evaluating echocardiographic RV function and morphology in healthy lowland adults at sea level and upon exposure to simulated altitude or high-altitude. Results: We included 37 studies in this systematic review, 12 of which used simulated altitude and 25 were conducted in high-altitude field conditions. Eligible studies reported at least one of the RV parameters, derived from the transthoracic echocardiographic assessment of RV systolic and diastolic function and RV morphology. The design of these studies significantly differed in terms of mode of high-altitude ascent, altitude level, duration of high-altitude stay, and timing of measurements. In the majority of the studies, echocardiographic examinations were performed within the first 10 days of high-altitude induction. Studies also differed widely by selectively reporting only a part of the multiple RV parameters. Despite consistent increase in PAP documented in all studies, reports on the RV function and morphology changes greatly differed between the studies. Conclusion: This systematic review revealed that the study reports on the effects of acute hypoxia on the RV were inconsistent and inconclusive. This may result from significantly different study designs, non-compliance with international guidelines on RV function assessment and limited statistical power due to small sample sizes. Moreover, the potential impact of other factors such as gender, age, ethnicity, physical activity, mode of ascent and environmental factors such as temperature and humidity on RV responses to hypoxia remained unexplored. Further research including large-scale prospective studies with improved designs and reproducible methods is needed to better understand RV responses to acute hypoxia exposure.